DOCTOR’S PERCEPTION OF THE ROLE OF PHARMACISTS IN CLINICAL PHARMACY SERVICES AT RSUP PROF. DR. R. D. KANDOU MANADO - Florence Jewelly Gabriella Raintama; Widya Lolo; Surya Sumantri Abdullah (PHARMACON, 2022)
In providing pharmaceutical services, collaboration between pharmacists and doctors is needed to improve therapeutic outcomes. For this reason, this study aims to describe doctors' perceptions about the role of pharmacists in carrying out pharmaceutical work at RSUP Prof. Dr. R. D. Kandou Manado in order to determine the extent to which doctors understand the pharmaceutical services provided by pharmacists. This research is a descriptive research with survey method and data processing is done quantitatively. Research respondents are doctors who work at RSUP Prof. Dr. R. D. Kandou Manado consisting of 75 respondents. The tool used in this research is a questionnaire using the Guttman scale which has been through validity and reliability tests. Data analysis was carried out by describing it in the form of a frequency distribution to find out how health workers perceive the role of pharmacists in pharmaceutical services at RSUP Prof. Dr. R.D. Kandou Manado. The results showed that doctors' perceptions tended to agree with the average value for opinions of 81.54% and for expectations of 94%. The conclusion of this study is that doctors have good opinions and expectations about the role of pharmacists in accordance with Pharmaceutical Service Standards.